Gender-Based Oppression and Sexual Exploitation of Female Contract Laborers in the Deli Tobacco Plantations, 1870–1930 - Lister Eva Simangunsong; Aggy Adinda Ginting; Naomi Magdalena Br Purba; Nita Pardede; Sonia Refinta Matanari (Mahesa Research Center (PT. Mahesa Global Publishing), 2026)
This study examines gender-based oppression and exploitation experienced by female contract laborers in the Deli tobacco plantations between 1870 and 1930. It explores how the colonial plantation system shaped women’s position and exposed them to social, economic, and sexual inequality. This research draws on a qualitative literature review of books, scholarly articles, historical reports, and other relevant historical sources. The findings show that female laborers occupied a subordinate position within the plantation workforce. They were assigned low-paid work, subjected to strict supervision, and received minimal labor protection. The gender imbalance within plantation communities also contributed to the expansion of prostitution, exposing women to sexual exploitation and serious social and health consequences. These findings demonstrate that the colonial plantation system exploited women not only economically but also through unequal gender relations and power structures embedded in the contract labor system. By centering women’s experiences, this study contributes to the historiography of women, labor, and colonialism in Indonesia.